2013
DOI: 10.1177/000348941312200304
|View full text |Cite
|
Sign up to set email alerts
|

New Method for in-Office Secondary Voice Prosthesis Insertion under Local Anesthesia by Reverse Puncture from Esophageal Lumen

Abstract: Most patients were treated with our new method with ease and at low risk. The high success rate and the absence of complications demonstrate the benefits of our method. We conclude that our method can be recommended for secondary reverse tracheoesophageal puncture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…In some cases, direct formation of the fistula is difficult and, thus, needs to be performed in a later stage. Indications are displayed in Table . This procedure is called a secondary TEP and used to be performed by using a rigid endoscope with the patient under general anesthesia .…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, direct formation of the fistula is difficult and, thus, needs to be performed in a later stage. Indications are displayed in Table . This procedure is called a secondary TEP and used to be performed by using a rigid endoscope with the patient under general anesthesia .…”
Section: Resultsmentioning
confidence: 99%
“…Although persons using T-E speech undergo speech rehabilitation to improve their speech quality [14], the performance index of speech rehabilitation for improving comprehensive QOL is yet to be determined. Given that our study revealed a correlation between comprehensive QOL and voice intensity, the latter can be a performance index for future speech rehabilitation studies.…”
Section: Discussionmentioning
confidence: 99%
“…As summarized in Table 1, the participants were 20 men with an average age of 70.8 years (SD, 9.2; range, 57-88). Two participants already had voice prostheses placed in a one-phase manner after total laryngectomy; however, 18 participants had voice prostheses placed by the two-phase Fukuhara method [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Septoplasties are well documented example of suitable operations for short-stay surgery under local anaesthesia [11,12] . In addition there are emerging new methods such as voice prosthesis insertion [13] and tracheooesophageal puncture [14] that require no general anaesthesia but can also be performed in local anaesthesia.…”
Section: Discussionmentioning
confidence: 99%